Pemanfaatan Multimedia dan Gaya Belajar dalam Meningkatkan Motivasi Belajar Siswa Kelas IV SD Negeri Larobenu - Gusasi, No’u; Lukman, Lukman; Jamaludin, Jamaludin; Misnah, Misnah; Ratu, Bau (Universitas Batanghari Jambi, 2024)
Low learning motivation certainly greatly affects learning outcomes and learning achievement. One of the factors that causes this to happen is the lack of use of multimedia in learning and the selection of multimedia that does not suit students' learning styles. This research aims to see how the use of multimedia and learning styles can increase learning motivation. This research use desciptive qualitative approach. Based on the research results, students' learning motivation increases with the use of multimedia that suits their learning style. This can be seen from the enthusiasm of students during teaching and learning activities in the classroom, the students' focus point is much higher, namely after paying attention to the teacher's explanation, the students' willingness to note down new things that are considered very important and easily understand or digest the learning material that has been studied.